2015
DOI: 10.3343/alm.2015.35.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Trimester-Specific Reference Intervals for Thyroid Hormones in Korean Pregnant Women

Abstract: BackgroundEstablishment of trimester- and assay-specific reference intervals for every population is recommended. The aim of this study was to establish a trimester- and assay-specific reference interval for thyroid-stimulating hormone (TSH) and free thyroxine (FT4) in Korean pregnant women.MethodsFrom April 2012 to December 2012, 531 pregnant women receiving prenatal care and 238 age-matched, non-pregnant women were enrolled in this study. After excluding patients with pregnancy-associated complications or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 35 publications
7
29
2
4
Order By: Relevance
“…The median level of TSH showed a signi cant increasing trend from the rst trimester to the third trimester: 1.36 (0.08-3.79) mIU/L for the rst trimester, 1.60 (0.12-3.95) mIU/L for the second trimester and 1.76 (0.38-4.18) mIU/L for the third trimester (P < 0.001). This study con rmed a clear trend of increasing TSH from the rst trimester to the third trimester in pregnant women [27].…”
Section: Discussionsupporting
confidence: 75%
“…The median level of TSH showed a signi cant increasing trend from the rst trimester to the third trimester: 1.36 (0.08-3.79) mIU/L for the rst trimester, 1.60 (0.12-3.95) mIU/L for the second trimester and 1.76 (0.38-4.18) mIU/L for the third trimester (P < 0.001). This study con rmed a clear trend of increasing TSH from the rst trimester to the third trimester in pregnant women [27].…”
Section: Discussionsupporting
confidence: 75%
“…[101112141516171819202122232425] Soldin et al . [15] showed that FT4 decreased from the 1 st to 3 rd trimester ( P < 0.001), but there was no significant difference between the second to the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al . [24] established trimester and assay specific 2.5 th –97.5 th levels of TFT in 531 pregnant Korean women using ECL immunoassay. The TSH reference intervals were 0.01–4.10, 0.01–4.26, and 0.15–4.57 mIU/L for the first, second, and third trimester, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies of pregnant women in the United States and Europe first led to recommendations for a TSH upper reference limit of 2.5 mIU/L in the first trimester and 3.0 mIU/L in the second and third trimesters [36]. During pregnancy, the Korean have demonstrated only a modest reduction in the upper reference limit [37].…”
Section: Main Issuementioning
confidence: 99%